Sex‐specific patterns of reproductive senescence in a long‐lived reintroduced raptor. (31st July 2018) - Murgatroyd, Megan; Roos, Staffan; Evans, Richard; Sansom, Alex; Whitfield, D. Philip; Sexton, David; Reid, Robin; Grant, Justin; Amar, Arjun
Abstract: For many species, there is evidence that breeding performance changes as an individual ages. In iteroparous species, breeding performance often increases through early life and is expected to level out or even decline (senesce) later in life. An individual's sex and conditions experienced in early life may also affect breeding performance and how this changes with age. Long‐term monitoring of individuals from reintroduced populations can provide unique opportunities to explore age‐related trends in breeding performance that might otherwise be logistically challenging. We used a unique dataset from a reintroduced population of white‐tailed eagles Haliaeetus albicilla in Scotland, which has been intensively monitored since their initial reintroduction in 1975, to study age‐ and sex‐specific trends in two measures of breeding performance. This monitoring provided data on the breeding performance of known individuals ranging in age from 3 to 26 years. We also explored changes in breeding performance in relation to early life experience (i.e., whether they were released or fledged in the wild). Breeding performance increased with age in early life in a similar manner for both sexes. We found stronger evidence for senescence in breeding performance in males than females. However, late‐life female breeding success was associated with early life experience, while male senescent trends were not apparently impacted by conditions experienced during early life. Sexual differences in senescence mean that older males are less likely to breed successfully compared to older females, and this may influence females' mate changes later in life. This difference may suggest a linked sexual difference in survival rates or the possibility of proactive partner change by females in later life in this typically monogamous biparental species. Abstract : This article uses a unique individual‐based long‐term dataset derived from the reintroduction of white‐tailed eagles in Scotland to examine sex‐specific trends in reproductive senescence. Male white‐tailed eagles age faster than females, possible evidence for toy‐boy relationships in later life.